Effects of seed priming with plant growth-promoting rhizobacteria on wheat yield and soil properties under contrasting soils. (21st October 2019) - Akbar, Muhammad; Aslam, Nazir; Khalil, Tayyaba; Akhtar, Shamim; Siddiqi, Ejaz Hussain; Iqbal, Muhammad Sajjad
Abstract: In the present investigation, different strains of Plant growth-promoting rhizobacteria (PGPR), namely Bacillus megaterium, Pseudomonas fluorescens and Bacillus subtilis were evaluated for their growth-promoting effects on wheat as well as on soil properties under field conditions at two different sites having sandy loam and silt loam type of soils. PGPR strains were evaluated either singly or in consortia. Amongst all the treatments, wheat inoculated with consortia was found most effective as it increased grain yield up to 53% over control in silt loam soil, whereas, corresponding effects in sandy loam soil were less pronounced as an increase of 31% was observed in corresponding treatments, respectively. Enhanced effects on soil properties were also more intense in silt loam as there was an increase of 205% organic matter as against sandy loam soil where this value was 110%.